Analisis Sistem Penyimpanan Arsip Aktif pada Kantor Biro Perencanaan Kementerian XYZ - Aisyah Chearani; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Archival activities have a very important role in every organization, both private and government. Archives have a role as a center of memory, a source of information and as a monitoring tool that is very necessary in every organization in the context of planning, analyzing, developing, formulating policies, making decisions and preparing accountability reports. Therefore, archives should be managed using a good system. This research aims to describe the existing archiving system at the Planning Bureau Office of the Ministry of XYZ. The focus of the problem in this research is the existing archiving system at the Planning Bureau Office of the Ministry of XYZ. In this research the author used a descriptive qualitative research approach. The data collection techniques used were observation, interviews and documentation. The results of this research show that the physical archive storage system at the Planning Bureau Office of the Ministry of The digital archive storage system used at the Planning Bureau Office of the Ministry of XYZ uses e-archives in the form of an application called SPASIKITA. Destruction of archives at the XYZ Ministry's planning bureau office depreciates inactive dynamic archives by destroying archives that no longer have any use value.